Jewish Text in Howard Fast’s Novel “Torquemada” - Vasiljeva, Elina; Hrapāne, Karolīna (Respectus Philologicus, 2024)
The present study aims to identify the specifics of the Jewish text in Howard Fast’s iconic novel Torquemada. The study is based on the semiotic definition of the text. The Jewish theme in the oeuvre of Fast, a writer of Jewish origin, occupies a significant place. The specific construction of the Jewish theme allows one to highlight the boundaries of a certain Jewish text in the author’s work, which was clearly formed during the period of ideological and national quest. The novel Torquemada occupies a special place in the Jewish text of Fast. The Jewish text of the novel Torquemada is represented by a multi-level model. At the anthological level, the Jewish text of the novel can be correlated with the ideological quests of the author, Howard Fast. However, at the same time, it is an allegoric narrative about the fate of the Jews of the 20th century and the tragedy of the Holocaust. The events of the 15th century are the allegory of the events of the 20th century, and the times of the Spanish Inquisition are associated with the tragedy of the Jews of Europe.